2004
DOI: 10.1002/jnr.20184
|View full text |Cite
|
Sign up to set email alerts
|

NGF acts via p75 low‐affinity neurotrophin receptor and calpain inhibition to reduce UV neurotoxicity

Abstract: The relative roles of the high-affinity nerve growth factor (NGF) receptor, TrkA, and low-affinity p75 neurotrophin receptor (p75NTR) in neuronal survival are an active research area. We reported previously that UV treatment induces a calpain-dependent, delayed neuronal death. We show here that NGF inhibits this UV-induced cortical neuron death. Interestingly, NGF neuroprotection requires p75NTR. Because it has been reported that NGF binding to p75NTR leads to ceramide generation, we evaluated whether ceramide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Growing evidence has shown that NGF induces neuronal survival with low-affinity binding to the p75 neurotrophin receptor (p75NTR) 54 . Additionally, it was shown that NGF-induced neuroprotection against OGD insult by inhibiting OGD-induced p38 activation 55 and against UV neurotoxicity by inhibiting calpain activity 56 . Furthermore, increased production of NGF in central nervous system (CNS) during diseases is able to suppress inflammation by switching the immune response to an anti-inflammatory 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has shown that NGF induces neuronal survival with low-affinity binding to the p75 neurotrophin receptor (p75NTR) 54 . Additionally, it was shown that NGF-induced neuroprotection against OGD insult by inhibiting OGD-induced p38 activation 55 and against UV neurotoxicity by inhibiting calpain activity 56 . Furthermore, increased production of NGF in central nervous system (CNS) during diseases is able to suppress inflammation by switching the immune response to an anti-inflammatory 57 .…”
Section: Discussionmentioning
confidence: 99%
“…MC192 has been used with this same purpose in several previous studies (e.g. Bui et al 2002; Numakawa et al 2003; McCollum & Estus, 2004). Figure 10 and shows that MC192 fully blocked the enhancement of HVA Ca 2+ current produced by a 60‐min exposure to NGF.…”
Section: Resultsmentioning
confidence: 99%
“…At variance with this, our data indicate that the effects of NGF on Ca 2+ currents in GH 3 cells are mediated by p75 in a TrkA‐independent way. Neither the early increase in the L‐type current nor the late increase in the T‐type current could be observed when NGF was applied in combination with MC192, an anti‐p75 antibody that has proved to be a valuable tool to identify p75‐mediated responses in rat neurons (Blochl & Sirrenberg, 1996; Numakawa et al 2003; McCollum & Estus, 2004) and PC12 cells (Bui et al 2002). By contrast, both increases persisted in the presence of K252a, a potent inhibitor of the tyrosine kinase activity of Trk receptors (Berg et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that calpains can promote tau fragmentation in AD and other disease contexts [25] and p75 NTR signaling can regulate calpain activity [50]. Activation of calpains results in cleavage of the 250 kDa cytoskeletal protein α-fodrin to fragments of ~ 145 kDa, and the ratio of the cleaved fragments to actin serves as a measure of calpain activity.…”
Section: Lm11a-31 Inhibits Calpain Activity and Activation Of Cdk5 Jmentioning
confidence: 99%